Information System for Distribution of Beach Tourism Sites in Gorontalo Province with Web-Based GIS - Aditya Lapu Kalua; Ade Yusupa; Sanriomi Sintaro; Erlica M.I. Tutu; Las D. Hutasoit (NUANSA INFORMATIKA, 2025)
Gorontalo Province, located at the northern tip of Sulawesi Island, has high tourism potential due to its natural and cultural richness, making it an attractive destination for both domestic and foreign tourists. However, to manage and promote this tourism potential effectively, accurate and easily accessible mapping is needed for tourists and related parties. The use of a web-based Geographic Information System (GIS) is an efficient solution in presenting complete information about tourist attractions in Gorontalo because changes to the data made can be more easily accessed with the dashboard menu. The goal is to improve the promotion and service of Gorontalo tourism through the development of this information system, actively contribute to improving the management and promotion of Gorontalo tourism, and become a guideline for the development of similar systems in other tourism sectors. The test results obtained using Blackbox testing obtained good test results and had a success rate of 96% so that the application can be used properly. It is hoped that the creation of a Gorontalo tourist attraction mapping information system will continue to be developed so that it is easily accessible to local and foreign tourists